COMPARATIVE STUDY OF THE EFFECTS OF IBUPROFEN AND CELAGRIP ON THE COURSE OF ASEPTIC INFLAMMATION INDUCED BY VARIOUS PHLOGOGENS IN THE PREPUBERTAL PERIOD (World Bulletin of Public Health, 2025)
The anti-inflammatory activity of Ibuprofen and CelAgrip was studied in a comparative aspect in prepubertal experimental animals. Inflammation in two-month-old rats was induced by subplantar injection of carrageenan, dextran, and histamine. In a separate series, the effects of the drugs on the proliferative phase of inflammation were studied using the "cotton pellet" model. It was found that both studied drugs significantly suppressed the inflammatory process in all models of aseptic inflammation induced by various phlogogens. Alongside exudation, the drugs also clearly suppressed the process of proliferation. No significant differences in the pharmacological activity of Ibuprofen and CelAgrip were identified, although the mechanisms of anti-inflammatory action of these drugs are presumed to differ. It is considered that CelAgrip can be used instead of Ibuprofen as an effective anti-inflammatory agent in pediatric practice.